[Karta pocztowa z wroną w klatce] . Postcard with a crow in a cage (Polska)
Multicolor print on white paper, with undivided back. Poster contains a graphic image which represents a crow in a cage. The crow is a symbol of Military Council of National Salvation, the governing body during Martial Law, whose Polish acronym resembles the word "crow" (WRON - wrona).